(untitled) (Kinesiology, 2018)
The purpose of the present study was to compare block periodization (BP) and daily undulating periodization (DUP) in eliciting changes in strength, jumping performance and throwing velocity in young male handball players. Fifteen players, of the same competitive level, were assigned to one of the periodization groups (DUP=9; BP=6). Pre- and post-tests included a one repetition maximum (1 RM) back squat, countermovement jump (CMJ), triple jump with the left and right leg, 20 m speed test, standing medicine ball throw, 7 m standing throw, and 9 m jumping throw. Strength training was performed twice a week throughout an 8-week period. The BP group performed training phases in the following order: hypertrophy, power strength and explosive strength; DUP alternated every week two sessions with a different focus. Total volume and intensity during the 8-week period were equal in both training groups. Despite both groups significantly improved 1 RM squat (33.3%, effect size [ES]=1.48 for DUP and 17.4%, ES=1.40 for BP) and triple jump (4-6.3%, ES=0.32-0.51 for DUP and 9.7-12.7%, ES=1.40 for BP) performance, greater gains (ES=0.96) were detected in DUP for the 9 m throwing velocity. No significant changes were found in either group for the 20 m sprint and CMJ. It can be concluded that both periodization programs elicited significant improvements in maximal strength and jumping performance in young male handball players, while DUP was more effective than BP on throwing velocity. Key words: strength, youth, team sport, training